Glucocorticoid-resistant asthma: more than meets the eye. (December 2013) - Reddy, Divya; Little, Frederic F.
Abstract Introduction: For decades glucocorticoids have been considered as the gold standard for the treatment of asthma. We present a case report of typical glucocorticoid-resistant asthma and current consensus in definitions of "severe refractory", "difficult" and "glucocorticoid-resistant" asthma. Methods: Full-text papers and abstracts were identified on the basis of a comprehensive literature search primarily in MEDLINE (1966 to June 2012) but also in the Cochrane Central Register of Controlled Trials database. Results: Glucocorticoid-resistant asthmatics are a small subset of patients who pose noteworthy diagnostic challenges while contributing disproportionately to health care costs. Recognition of various asthma phenotypes has aided in characterizing groups with severe asthma and given a better understanding of its pathophysiological process. The molecular mechanism of glucocorticoid action is complicated and several pathways have been identified to explain drug resistance, which in turn is crucial for drug development. Tobacco smoking appears to be the single most important contributor of glucocorticoid resistance. We present the emerging and promising concepts in the management of glucocorticoid-resistant asthma, which mainly include drugs targeting specific molecules, receptors, inflammatory cells or immune processes. Conclusion: The challenges in making a diagnosis of glucocorticoid-resistant asthma may contribute to underestimating its prevalence and impact on patient care. Considerable progress has been made in identifying distinct phenotypes and mechanisms of glucocorticoid resistance; therefore the future of new drug development in management of asthma is promising.